2021
DOI: 10.3389/fphys.2021.700246
|View full text |Cite
|
Sign up to set email alerts
|

L-Leucine Improves Metabolic Disorders in Mice With in-utero Cigarette Smoke Exposure

Abstract: Objectives: Maternal cigarette smoke exposure (SE) causes intrauterine undernutrition, resulting in increased risk for metabolic disorders and type 2 diabetes in the offspring without sex differences. L-leucine supplementation has been shown to reduce body weight and improve glucose metabolism in both obese animals and humans. In this study, we aimed to determine whether postnatal L-leucine supplementation in female offspring can ameliorate the detrimental impact of maternal SE.Methods: Female Balb/c mice (6-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…A previous study showed that quercetin transiently increased energy expenditure in mice, 27 and l -leucine was closely connected with energy balance. 28,29 Consistent with the literature, we found that “cholesterol metabolism (hsa04979)” and “glycerophospholipid metabolism (hsa00564)” were enriched during the integrated proteomics and metabolomics analysis. Taken together, our observations suggest that Roxadustat may regulate blood lipid levels by controlling the lipid metabolic pathways in renal anemia patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A previous study showed that quercetin transiently increased energy expenditure in mice, 27 and l -leucine was closely connected with energy balance. 28,29 Consistent with the literature, we found that “cholesterol metabolism (hsa04979)” and “glycerophospholipid metabolism (hsa00564)” were enriched during the integrated proteomics and metabolomics analysis. Taken together, our observations suggest that Roxadustat may regulate blood lipid levels by controlling the lipid metabolic pathways in renal anemia patients.…”
Section: Discussionsupporting
confidence: 88%
“…Metabolomics-based investigations revealed that Roxadustat changed the levels of urine metabolites related to fat metabolism, such as Quercetin and L-Leucine. A previous study showed that quercetin transiently increased energy expenditure in mice 27 , and L-Leucine was closely connected with energy balance 28,29 . Consistent with the literature, we found that "Cholesterol metabolism (hsa04979)" and "Glycerophospholipid metabolism (hsa00564)" were enriched during the integrated proteomics and metabolomics analysis.…”
Section: The Lipid-lowering Effect Of Roxadustatmentioning
confidence: 95%
“…Liver is a critical organ for amino acid homeostasis, thereby confirming with our findings of declined levels of a series of amino acids in the SiNPs-administered liver and highlighting how disturbed amino acid metabolism can exacerbate hepatic injury. It is increasingly recognized that abnormality in amino acids could potentially impact energy metabolism, protein synthesis and proteolysis, fatty acid and urea synthesis, and cell signaling [ [54] , [55] , [56] , [57] ]. Increased evidence suggested a close link between imbalanced amino acid homeostasis and liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have gradually revealed the roles of amino acids in oxidative stress and liver diseases. For example, l -Leucine could protect DNA damage from oxidative stress as a free radical scavenger [ 88 ], and reverse fat accumulation and metabolic disorder in Balb/c mice caused by cigarette [ 57 ]. Gamma aminobutyric acid (GABA) can reduce the oxidative stress and prevent obesity in C57BL/6 mice fed with HFD [ 89 ].…”
Section: Discussionmentioning
confidence: 99%